The spectrum of response to erenumab in patients with chronic migraine and subgroup analysis of patients achieving ≥50%, ≥75%, and 100% response. (January 2020) - Brandes, Jan Lewis; Diener, Hans-Christoph; Dolezil, David; Freeman, Marshall C; McAllister, Peter J; Winner, Paul; Klatt, Jan; Cheng, Sunfa; Zhang, Feng; Wen, Shihua; Ritter, Shannon; Lenz, Robert A; et al.
Objective: To assess the efficacy of erenumab across the spectrum of response thresholds (≥50%, ≥75%, 100%) based on monthly migraine days (MMD) reduction in patients with chronic migraine from a 12-week, randomized study (NCT02066415). Methods: Patients (n = 667) received (3:2:2) placebo or erenumab 70/140 mg once-monthly. The proportion of patients achieving a given response threshold was assessed. A post-hoc analysis was conducted to contextualize the actual treatment benefit in subgroups of patients achieving (or not) specified response thresholds. Outcome measures included MMD, acute migraine-specific medication treatment days (MSMD) and disability. Results: The proportion of patients responding to erenumab exceeded that of placebo at the ≥50% and ≥75% response thresholds. At month 3, 39.9% and 41.2% of patients on erenumab 70 and 140 mg, respectively, achieved ≥50% response versus placebo (23.5%). Similarly, at month 3, 17.0% and 20.9% of patients on erenumab 70 and 140 mg, respectively, achieved ≥75% response versus placebo (7.8%). Compared with the overall erenumab-treated population (change in MMD: −6.6 [both 70 and 140 mg]), ≥50% responders showed MMD reductions of −12.2/−12.5 for 70 mg/140 mg versus −2.6/−2.2 for those not achieving ≥50% response. ≥75% responders showed MMD reductions of −13.9/−14.8 for 70 mg/140 mg versus −5.0/−4.3 for those not achieving ≥75% response. Relative improvements in MSMD and disability were observed in responders versus overall erenumab-treated population. Conclusion: For erenumab-treated patients achieving ≥50% response, the actual reduction in MMD was almost twice that of the overall population. These findings provide context for setting realistic expectations regarding actual treatment benefit experienced by patients responding to treatment.